Sosialisasi Kelas Agama bagi Orang Tua Anak Berkebutuhan Khusus di Bimbingan Belajar Buah Hati - Fitriatun, Erna; Susilawati, Indri; Sukarman (Insan Kreasi Media, 2024)
Facilitating the integration of religious education for parents of children with special needs is a crucial component of delivering services aimed at introducing Islam and fostering the development of religious interests and talents. This program is driven by the recognition that parents of children with special needs encounter challenges in facilitating religious education and nurturing their skills, particularly in the area of memorizing the Qur'an. The socialization method employed employs a personalized and participatory approach with each parent, aimed at enhancing their comprehension of how to administer religious classes and demonstrate religious class activities effectively. The primary emphasis is on teaching letters or Makhorijul letters. The examination results indicated a rise in parents' comprehension of how to educate children with special needs in matters of religion.